The Effect Of Contextual Learning Model Based on Outing Clas on The Learning Outcomes of Class V students - Dewi, Risma; Mulyadi, Mulyadi; Syam, Nur (ALENA : Journal of Elementary Education, 2025)
The purpose of this research is to describe how the Outing Class-based contextual learning model is applied, describe the learning outcomes of students in the Natural and Social Sciences (IPAS), and ascertain the impact of the Outing Class-based contextual learning model on the learning outcomes of fifth-grade students at SD Inpres Kalang Tubung II Makassar City. This kind of study uses the Pre-Experimental Design research approach and is a one-group presetest-posttest design. There were 41 pupils in the fifth grade at SD Inpres Kalang Tubung II Makassar City that made up the study's population. Class V B students made up the study's sample, consisting of 22 individuals, 15 of whom were male and 7 of whom were female. The findings revealed that: 1) A summary of how the Outing class-based contextual learning methodology is applied. When this strategy is used, students participate in extracurricular learning activities that are closely linked to the idea or subject matter being studied. Students that participate in outing class activities become more engaged in their education and gain a better understanding of the connection between theory and practice. 2) A summary of the Natural and Social Sciences (IPAS) learning outcomes based on the pretest scores, where students' average score is 60. Additionally, the average posttest score is 85, indicating that students' IPAS learning outcomes following the implementation of the contextual learning model based on outing classes are better than those prior to the implementation of.